The Application of Knowledge Management in The United States Agency for International Development ( USAID ) - Hendrawan, Muhammad Rosyihan (Record and Library Journal, 2016)
This study aims to find out the implementation of Knowledge Management by The United States Agency for International Development (USAID). The other goal of this study is to determine why USAID tries to develop KM. This study was done by using a literature review method with descriptive analyses. Data was collected by documents analyses. This result of the study shows that knowledge management (KM) has a strategic and vital position to the existence of USAID. USAID has been Able to run continuously through the KM division specifically created to carry out a series of policies that have been determined by the USAID. As a worldwide organization, USAID has been very worth implementing its own strategic system in an effort to reach every knowledge management of the latest and dynamic information so that it can be an organizations intellectual assets for sustainability in the era of globalization. Expected with the implementation of KM system will be Able to improve the performance of the organization so that it has a competitive advantage in the face of global competition.